Forensic Monitoring Project Report: Bučići Recovery Report Swedish Forensic Team - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Harrington, Richard On 21 October 1998 a Swedish team of forensic experts conducted a recovery effort in the vicinity of Bučići. The purpose of the operation was to recover the remains of a Swedish mercenary who was killed in July of 1993. No remains were found. Swedish authorities sought to recover the body of Lars-Erik Muhrbeck, a Swedish mercenary employed by the Bosnian Croatian army (HVO). He is beileved to have been killed by one or more fellow mercenaries in July of 1993. Place of Exhumation: Bučići Exhumation Site: Duvno Date of Exhumation: 21 October 1998 Minimum Number of Exhumed Individuals: 000